Structure relations for orthogonal polynomials on the unit circle - Branquinho, A. (2020)
Structure relations for orthogonal polynomials on the unit circle are studied. We begin by proving that semi-classical orthogonal polynomials on the unit circle satisfy structure relations of the following type: [...]